Restorative Justice in Law Enforcement of Banking Crimes : How it's Works? - Harrieti, Nun; Mantili, Rai; Bunga, Dewi; Manap, Norhoneydayatie Abdul (Jambura Law Review, 2026)
The escalating complexity of contemporary banking crimes is fundamentally catalyzed by the rapid evolution of digital technologies and the extensive globalization of financial transaction.   The Financial Services Authority's Annual Report shows an increase in the number of resolved banking crimes in 2023, from 13 (thirteen) cases to 18 (eighteen) in 2024. The principle of restorative justice, which prioritizes restoring the condition of the injured party, has become a new concept in enforcing banking crime law, apart from the criminal sanctions that has been applied. It is of particular interest to undertake research regarding how the principle of restorative justice is applied in the current law enforcement of banking crimes. This research engages normative juridical approach with analytical descriptive specifications. The application of the restorative justice principle in enforcing banking crime law is through a non-prosecution mechanism which provides an opportunity for parties suspected of committing banking crimes at the investigation stage to apply for resolution of violations of laws and regulations in the banking sector to the Financial Services Authority. Once the Financial Services Authority investigator approves the application, the applicant is obliged to carry out the agreement (non-prosecution agreement) including paying compensation and then the case is stopped and not continued to the investigation stage. The establishment of transparent standards and objective benchmarks is imperative for the Financial Services Authority in adjudicating settlement petitions for violations to guarantee legal certainty.